2010
DOI: 10.3791/2041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ultrasonic Vocalizations During Drug Self-administration in Rats

Abstract: Drug self-administration procedures are commonly used to study behavioral and neurochemical changes associated with human drug abuse, addiction and relapse. Various types of behavioral activity are commonly utilized as measures of drug motivation in animals. However, a crucial component of drug abuse relapse in abstinent cocaine users is "drug craving", which is difficult to model in animals, as it often occurs in the absence of overt behaviors. Yet, it is possible that a class of ultrasonic vocalizations (USV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The relationship between calls and movement in this case might arise not because the locomotion is causally producing the calls, but because both locomotion and calling are indicative of elevated positive affective. This explanation is consistent with the effects of amphetamine and cocaine, which elicit robust increases in 50-kHz vocalizations and activity levels [ 50 , 51 ], with high frequencies of calls being emitted whether the rats are moving or not [ 52 ]. On the other hand, the affective communication hypothesis offers no explanation for the specific relationships between calls and actions shown in Fig 3 .…”
Section: Discussionsupporting
confidence: 78%
“…The relationship between calls and movement in this case might arise not because the locomotion is causally producing the calls, but because both locomotion and calling are indicative of elevated positive affective. This explanation is consistent with the effects of amphetamine and cocaine, which elicit robust increases in 50-kHz vocalizations and activity levels [ 50 , 51 ], with high frequencies of calls being emitted whether the rats are moving or not [ 52 ]. On the other hand, the affective communication hypothesis offers no explanation for the specific relationships between calls and actions shown in Fig 3 .…”
Section: Discussionsupporting
confidence: 78%
“…We used ultrasonic vocalizations (USVs) in the range of 50 kHz to investigate the affective response to heroin and cocaine in the rat. It has been reported that rats emit 50-kHz USVs when exposed to natural rewarding stimuli (White et al 1990;Knutson et al 1998;Panksepp and Burgdorf 2000;Burgdorf et al 2000) as well as to addictive drugs (Knutson et al 1999;Maier et al 2010). Consistent with the arousal state mismatch hypothesis, we found that at home, rats emit more 50-kHz USVs when self-administering heroine than when self-administering cocaine (Fig.…”
Section: The Affective Response To Cocaine and Heroin Is Influenced Isupporting
confidence: 86%
“…In line with this hypothesis, it has been shown that a dissociation exists between the emission of 50-kHz USVs and behavioral measures of affective responses during drug self-administration or anticipation. Thus, while 50-kHz USVs can be elicited by administration of psychostimulant drugs (Barker et al 2010;Browning et al 2011;Burgdorf et al 2000;Burgdorf and Panksepp 2006;Knutson et al 1998;Maier et al 2010;Simola et al 2012;Thompson et al 2006;Trezza et al 2010;Wintink and Brudzynski 2001), rewarding doses of morphine, MDMA, and nicotine have been related to no changes or even decreases in 50-kHz USV emission (Hamed et al 2012;Sadananda et al 2012;Simola et al 2012;Wright et al 2012).…”
Section: Discussionmentioning
confidence: 98%